Chromatin remodeling enzyme Snf2h regulates embryonic lens differentiation and denucleation - He, Shuying; Limi, Saima; McGreal, Rebecca S; Xie, Qing; Brennan, Lisa A; Kantorow, Wanda Lee; Kokavec, Juraj; Majumdar, Romit; Hou, Harry; Edelmann, Winfried; Liu, Wei; Ashery-Padan, Ruth; et al. (Development, 2016)
Ocular lens morphogenesis is a model for investigating mechanisms of cellular differentiation, spatial and temporal gene expression control, and chromatin regulation. Brg1 (Smarca4) and Snf2h (Smarca5) are catalytic subunits of distinct ATP-dependent chromatin remodeling complexes implicated in transcriptional regulation. Previous studies have shown that Brg1 regulates both lens fiber cell differentiation and organized degradation of their nuclei (denucleation). Here, we employed a conditional Snf2h(flox) mouse model to probe the cellular and molecular mechanisms of lens formation. Depletion of Snf2h induces premature and expanded differentiation of lens precursor cells forming the lens vesicle, implicating Snf2h as a key regulator of lens vesicle polarity through spatial control of Prox1, Jag1, p27(Kip1) (Cdkn1b) and p57(Kip2) (Cdkn1c) gene expression. The abnormal Snf2h(-/-) fiber cells also retain their nuclei. RNA profiling of Snf2h(-/) (-) and Brg1(-/-) eyes revealed differences in multiple transcripts, including prominent downregulation of those encoding Hsf4 and DNase IIβ, which are implicated in the denucleation process. In summary, our data suggest that Snf2h is essential for the establishment of lens vesicle polarity, partitioning of prospective lens epithelial and fiber cell compartments, lens fiber cell differentiation, and lens fiber cell nuclear degradation.
Keywords: mutace; DNA vazebné proteiny; oční čočka; mitofagie; Animals; Nuclear Proteins; biologické modely; Cell Compartmentation; Mitophagy; Female; Autophagy; Embryo, Mammalian; jaderné proteiny; transkripční faktory; Gene Expression Regulation, Developmental; ženské pohlaví; Mice, Knockout; myši knockoutované; Cell Cycle; Lens, Crystalline; buněčná diferenciace; Cell Nucleus; Models, Biological; Epithelial Cells; DNA Helicases; Transcription Factors; adenosintrifosfatasy; Chromosomal Proteins, Non-Histone; Mutation; kompartmentace buňky; buněčný cyklus; autofagie; buněčné jádro; restrukturace chromatinu; DNA-Binding Proteins; chromozomální proteiny, nehistonové; transkripční faktor PAX6; PAX6 Transcription Factor; transkriptom; Cell Differentiation; zvířata; Transcriptome; Adenosine Triphosphatases; DNA-helikasy; embryo savčí; vývojová regulace genové exprese; epitelové buňky; Chromatin Assembly and Disassembly